Odpowiedź :
Odpowiedź:
a) x + 9 = 17 to x = 17 - 9 = 8
b) x - 16 = 90 to x = 90 + 16 = 106
c) 70 - z = 69 to - z = 69 - 70 = - 1 to z = 1
d) 15 + x = 15 to x = 0
e) x : 7 = 14 to x/7 = 14 /•7 to x = 98
f) 2x = 18 to x = 18/2 = 9
g) 5x = 100 to x = 100/5 = 20
h) x + 19 = 25 to x = 19 - 25 = 6
i) z + 14 = 21 to z = 21 - 14 = 7
j) y - 15 = 31 to y = 31 + 15 = 46
k) a - 5 = 4 to a = 4 - 5 = 9
l) 3 + x = 2 to x = 2 - 3 = - 1
m) 5a = 2 to a = 2/5
n) 4a = 16 to a = 16/4 = 4
Szczegółowe wyjaśnienie:
[jak coś źle przeczytam to nie moja wina]
a) x + 9 = 17 to x = 17 - 9 = 8
b) x - 16 = 90 to x = 90 + 16 = 106
c) 70 - z = 69 to - z = 69 - 70 = - 1 to z = 1
d) 15 + x = 15 to x = 0
e) x : 7 = 14 to x/7 = 14 /•7 to x = 98
f) 2x = 18 to x = 18/2 = 9
g) 5x = 100 to x = 100/5 = 20
h) x + 19 = 25 to x = 19 - 25 = 6
i) z + 14 = 21 to z = 21 - 14 = 7
j) y - 15 = 31 to y = 31 + 15 = 46
k) a - 5 = 4 to a = 4 - 5 = 9
l) 3 + x = 2 to x = 2 - 3 = - 1
m) 5a = 2 to a = 2/5
n) 4a = 16 to a = 16/4 = 4